Characterisation of fast dispersible fruit tablets made from green and ripe mango fruit powders - Ong, M. Y.; Yusof, Yus Aniza; Aziz, Mohammad Gulzarul; Chin, Nyuk Ling; Mohd. Amin, Nor Amaiza (Elsevier, 2014)
This study was performed to assess the compressibility and dissolution of binary fruit tablets prepared from whole green and ripe mango powder influenced by disintegrants. Mango powder was prepared by freeze-drying mango pulps. Green mango powder exhibited medium flow and was poorly compressible compared with ripe and mixed mango powders. Tabletting of powders was performed using a uniaxial die compaction machine and dissolution tester with a moving paddle for the dissolution study. Among five formulations, the tensile strength of the mixed tablets was higher than the individual and mixed-fruit tablets. The dissolution kinetics revealed that the dissolution rate of the mixed-fruit tablets was highly influenced by the disintegrant content. In conclusion, mixed mango tablets can be used as an effective vitamin C supplement if the formulation is optimised with balanced sweetness and acidity and can easily be consumed by chewing or by dissolving in water.